(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze the role of the Jeneponto District Attorney’s Office in implementing the principle of reverse burden of proof in corruption cases, and to identify factors that influence the success or obstacles in implementing the principle. The method used is an empirical method with a legal approach, namely combining observations of legal practices with normative studies. The results of the study indicate that although the principle of proof is legally recognized in Indonesia through Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, its implementation is still limited and faces obstacles, such as minimal transparency and lack of technical understanding in the field. This study concludes that to optimize the principle of reverse burden of proof, improvements are needed in terms of legal substance, human resources, and synergy between law enforcement agencies. Abstrak Penelitian ini bertujuan untuk menganalisis peran Kejaksaan Negeri Jeneponto dalam penerapan asas pembuktian terbalik dalam perkara tindak pidana korupsi, serta mengidentifikasi faktor-faktor yang mempengaruhi keberhasilan atau kendala penerapan asas tersebut. Metode yang digunakan adalah metode empiris dengan pendekatan hukum, yang memadukan pengamatan terhadap praktik hukum dengan kajian normatif. Hasil penelitian menunjukkan bahwa meskipun pembuktian terbalik diakui secara hukum di Indonesia melalui Undang-Undang Nomor 31 Tahun 1999 jo. Undang-Undang Nomor 20 Tahun 2001, penerapannya masih terbatas dan menghadapi kendala, seperti minimnya transparansi serta kurangnya pemahaman teknis di lapangan. Studi ini menyimpulkan bahwa optimalisasi asas pembuktian terbalik membutuhkan perbaikan dari segi substansi hukum, sumber daya manusia, dan sinergi antarlembaga penegak hukum.